Cocrystals/salts of Furosemide : Interesting case of colour cocrystal polymorphism - Sangtani, Ekta; Jha, Kunal; Munshi, Parthapratim; Gonnade, Rajesh (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Color cocrystal polymorphism; Sandwich assembly; Stacking interactions

Furosemide cocrystals with pyridines: an interesting case of color cocrystal polymorphism - Sangtani, Ekta; Sahu, Sanjay Kumar; Thorat, Shridhar H.; Gawade, Rupesh L.; Jha, Kunal K.; Munshi, Parthapratim; Gonnade, Rajesh G. (Crystal Growth & Design, 2015)
Furosemide (FS), a loop diuretic drug commonly used for the treatment of hypertension and edema, exhibited color cocrystal polymorphism with coformer 4,4'-bipyridine (4BPY) in the stoichiometry 2:1, albeit both the API and the cocrystal former are colorless. Crystallization from ethanol, isopropanol, ethanol-water (v/v, 1/1) mixture, and acetonitrile yielded pale yellow (form II, thin needles) and orange (form 1II, blocks) cocrystals concomitantly. Needles appeared from solution within a day, while the blocks were obtained after 1-2 days from the same flask, indicating that yellow needles were formed faster and the orange blocks were perhaps formed under thermodynamic conditions. Form 1I cocrystals could also be produced from the variety of common solvents. Cocrystallization of FS with 2,2'-bipyridine (2BPY) and 4-aminopyridine (4AP) gave colorless cocrystals 2 and 3, respectively, and did not exhibit polymorphism. The single-crystal X-ray structures, powder X-ray diffraction, photophysical characterization, differential scanning calorimetry, hot stage microscopy studies, and density functional theory (DFT) calculations provide insight into the structure property relationship. The common structural features observed in all of the structures is the formation of sandwich motifs comprising FS and pyridines through pi-stacking interactions. These motifs are linked differently through hydrogen bonding interactions in all three directions. The significant color difference between the two cocrystals dimorphs could be attributed to the different pi-stacking patterns and hydrogen bonding interactions between molecules of FS and 4BPY in their cocrystal structures. Investigation on the origin of the color difference using DFT calculations revealed the decrease in HOMO-LUMO gap for form 1II cocrystals (orange) compared to form 1I crystals (light yellow). The crystal-to-crystal thermal transformation of form 1I crystals to form 1II crystals of 1 suggests the role of pi-stacking assemblies in driving the self-assembly.

Synthesis of novel N-cyclopentenyl-lactams using the aube reaction - Shinde, Madhuri V.; Ople, Rohini S.; Sangtani, Ekta; Gonnade, Rajesh G.; Reddy, D. Srinivasa (Beilstein Journal of Organic Chemistry, 2015)
A novel and convenient method utilizing the Aube reaction to access a new class of compounds that are similar to carbocyclic nucleosides is reported. The azido alcohol derived from Vince lactam undergoes the Aube reaction with various cyclic ketones to give cyclopentenyl-substituted lactams. Upon dihydroxylation, this affords the N-cyclopentenyl-lactam compounds in racemic form. Given the numerous uses of nucleosides and related compounds, we were interested in the synthesis of carbocylic nucleoside mimics. The attempts and results are described herein.
Keywords: Aube reaction; Biological activity; carbocyclic nucleosides; cyclopentenylated lactams; cyclopentylated lactams

Additive mediated syn-anti conformational tuning at nucleation to capture elusive polymorphs: remarkable role of extended pi-stacking interactions in driving the self-assembly - Gawade, Rupesh L.; Chakravarty, Debamitra K.; Kotmale, Amol; Sangtani, Ekta; Joshi, Pranaya V.; Ahmed, Awais; Mane, Manoj V.; Das, Susanta; Vanka, Kumar; Rajamohanan, Pattuparambil R.; Puranik, Vedavati G.; Gonnade, Rajesh G. (Crystal Growth & Design, 2016)
Understanding the process of prenucleation clustering at supersaturating stage is of significant importance to envisage the polymorphism in crystalline materials. Preferential formation of a thermodynamically stable crystal form suggests energetically favored patterns of interactions which control molecular aggregation during nucleation. Introduction of additives during crystallization is sometimes used as a suitable strategy to obtain metastable polymorphs in cases where it is not easy to capture the same by conventional crystallization methods. Comparative analysis of energy relationships and intermolecular interactions between thermodynamically stable and metastable crystal forms provides valuable clues about the nature of growth synthons at prenucleation clustering and preferential crystallization of the thermodynamic form. Conformationally flexible sulfonamide/sulfoester derivatives constituting electron rich and electron deficient aromatic rings were synthesized to study the interplay between pi-stacking and hydrogen bonding synthons. We have identified and characterized the thermodynamically stable and metastable elusive polymorphs of aromatic sulfonamides 1 and 2 and sulfoesters 3 and 4. However, these compounds eluded polymorphism during crystallisation from various common solvents/conditions and only produced thermodynamically stable crystals forms (form I crystals). Surprisingly, exploitation of pyrazinamide as an additive in different stoichiometric ratios during crystallization gave elusive polymorphs [three for 1 (form 1II, form 1III, and form 1IV) and one each for 2 (form 2II), 3 (form 3II), and 4 (form 4II)]. Molecules in stable crystal forms of these compounds are linked via extended chains of parallel displaced pi...pi stacking interactions that seem to play a vital role in driving the self-assembly of molecules and subsequently governing the nucleation process. In contrast, molecules in metastable polymorphs are devoid of such extended pi-stacking assemblies. Interestingly, differential scanning calorimetry, hot stage microscopy, and X-ray crystallographic studies confirmed the thermal crystal-to-crystal transition of all three metastable polymorphs of 1 (form 1II, form 1III, and form 1IV) to its thermodynamically stable crystal form (form 1I). Conformational analysis of molecule 1 using density functional theory calculations also validated higher stability for syn conformation (observed in Form 1I crystals) over anti and midway conformations (seen in metastable polymorphs). Melt crystallization of form 1I crystals of 1 on the larger face (001) of delta-pyrazinamide and lattice matching analysis (GRACE) revealed that the layered arrangement of molecules of delta-pyrazinamide (on 001 face) during heterogeneous nucleation acts as a template (heteroepitaxy) to provide a preferential site for the nucleation of new metastable polymorphs by selectively inhibiting the most preferred crystal form from growing into the nucleus. Solution state one- and two-dimensional (NOESY) H-1 NMR, scanning electron microscopy, and a Cambridge Structural Database survey were conducted to substantiate the role of additives during crystallization.

Residue dependent hydrogen-bonding preferences in orthanilic acid-based short peptide beta-turn motifs - Jedhe, Ganesh S.; Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Sangtani, Ekta; Shinde, Dinesh R.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (RSC Advances, 2016)
This communication describes the competition between native beta-turn (C10) and 2-aminobenzenesulfonic acid (SAnt)( orthanilic acid)-based pseudo beta-turn (C11) in their hybrid peptides. Solid-state crystal structure and solution-state NMR studies revealed that C10 and C11 can be simultaneously observed under appropriate conditions. The variable temperature NMR coefficient data suggest that the isolated C11/C14 hydrogen bond is weaker in comparison with the consecutive C10 and C11 turns.

Polymorphs and cocrystals: a comparative analysis - Gonnade, Rajesh G.; Sangtani, Ekta (Journal of the Indian Institute of Science, 2017)
Controlling polymorphism has been the subject of vigorous research in the recent past in the pharmaceutical industry due to the distinct physicochemical properties associated with each solid form. Developing cocrystals/salts of active pharmaceutical ingredients (APIs) has gained tremendous research interest in recent years owing to their potential to improve pharmaceutically relevant properties without affecting therapeutic efficacy. It is observed that compounds that exhibit polymorphism and also contain several H bond donor/acceptor groups have a tendency to form cocrystals and sometime even display cocrystal polymorphism, although this tendency cannot be generalized. The aim of this contribution is to correlate crystal structures of some polymorphic APIs and their respective cocrystals to understand the rationale behind a polymorphic compound generating cocrystals. Here, we make an attempt to compare how the conformation of the molecule observed in its polymorphs support the generation of cocrystals/salts. We understand that it is impossible to cover all the polymorphs and their cocrystals/salts available in the CSD; the comparative study has been carried out with a few case studies, wherein APIs displayed polymorphism (conformation) and also formed cocrystals/salts.

Salts and cocrystals of furosemide with pyridines: differences in π-Stacking and color polymorphism - Sangtani, Ekta; Mandal, Suman Kumar; Sreelakshmi, A. S.; Munshi, Parthapratim; Gonnade, Rajesh G. (Crystal Growth & Design, 2017)
Furosemide (FS), a loop diuretic drug that has a potential to exhibit polymorphism, produced color polymorphs of orange (form 1I) and yellow (form 1II) concomitantly with coformer 1, 2-bis(4-pyridyl)ethylene. However, cocrystallization of FS with other pyridines yielded colorless salts (2 and 4) and cocrystals (3 and 5). The significant color difference between the two polymorphs (forms 1I and 1II) could be attributed to the dissimilar π-stacking patterns between the two components and differences in their highest occupied molecular orbital−lowest unoccupied molecular orbital gap. The molecular packing of form 1I and 2 is very similar, but 2 is colorless due to lack of extended π-conjugation.

Unprecedented solvent induced inter-conversion between monomeric and dimeric silylene-zinc iodide adducts - Yadav, Sandeep; Sangtani, Ekta; Dhawan, Diksha; Gonnade, Rajesh G.; Ghosh, Debashree; Sen, Sakya S. (Dalton Transaction, 2017)
<div class="block-record-info" style="margin: 0px 22px 22px; list-style: none; padding: 0px; line-height: 20px; font-size: 13px; color: rgb(51, 51, 51); font-family: arial, helvetica, sans-serif; background-color: rgb(248, 248, 248);"> Usually, when a silylene reacts with a transition metal Lewis acid, it forms an adduct which could be either monomeric or dimeric. However, we present here that a silylene, [PhC(NtBu)(2)SiN(SiMe3)(2)] can form both monomeric [PhC(NtBu)(2)Si{N(SiMe3)(2)} -> ZnI2]center dot THF (1) and dimeric [{PhC(NtBu)(2)}(N(SiMe3)(2))SiZnI,(mu-I)](2) (2) adducts upon reaction with ZnI2. The formation of 1 and 2 relies upon the solvent used for the reaction or crystallization. When the crystallization is carried out in THF complex 1 is formed, however, when the reaction and crystallization are performed in acetonitrile complex 2 is obtained. Both 1 and 2 were structurally authenticated and the nature of the Si-Zn bond in these complexes was determined by quantum chemical calculations. In addition, a spontaneous inter-conversion between 1 and 2 just by changing the solvents has been also observed; a feature presently not known for silylene-transition metal Lewis adducts.
Keywords: Bis(Silylene ); Carbene Complexes; Crystal -structure Determination; Dative bond; Lewis acid base reaction; Ligands; Main- group compounds; Reactivity; Silicon(II) Bis(Trimethylsilyl)Amide; Carbonyl-Complexes

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

Antidiabetic activity of dihydropyrimidine scaffolds and structural insight by single crystal x-ray studies - Bairagi, Keshab M.; Younis, Nancy S.; Emeka, Promise M.; Sangtani, Ekta; Gonnade, Rajesh G.; Venugopala, Katharigatta N.; Alwassil, I. Osama; Khalil, Hany E.; Nayak, Susanta K. (Medicinal Chemistry, 2020)
Background: This research project is designed to identify the anti-diabetic effects of the newly synthesized compounds to conclude the perspective of consuming one or more of these new synthetic compounds for diabetes management. Introduction: A series of dihydropyrimidine (DHPM) derivative bearing electron releasing and electron-withdrawing substituent's on phenyl ring (a-j) were synthesized and screened for antihyperglycemic(anti-diabetic) activity on streptozotocin (STZ) induced diabetic rat model. The newly synthesized compounds were characterized by using FT-IR, melting point, H-1 and C-13 NMR analysis. The crystal structure and supramolecular features were analyzed through single-crystal X-ray study. Anti-diabetic activity testing of newly prepared DHPM scaffolds was mainly based on their relative substituent on the phenyl ring along with urea and thiourea. Among the synthesized DHPM scaffold, the test compound c having chlorine group on phenyl ring at the ortho position to the hydropyrimidine ring with urea and methyl acetoacetate derivative shows moderate lowering of glucose level. However, the title compounds methyl 4-(4-hydroxy-3-methoxyphenyl)-6-methyl-2-thioxo-1,2,3,4-tetrahydropyrimi dine-5-carboxylate(g) and ethyl 4-(3-ethoxy-4-hydroxyphenyl)-6-methyl-2-oxo-1,2,3,4-tetrahydroprimidine- 5-carboxylate(h) having methoxy and ethoxy substituents on phenyl ring show significant hypoglycemic activity compared to the remaining compounds from the Scheme 1. Methods: The experimental rat models for the study were divided into 13 groups (n = 10); group 1 animals were treated with 0.5% CMC (0.5mL) (vehicle); group 2 were considered the streptozotocin (STZ)/nicotinamide diabetic control group (DC) and untreated, group 3 diabetic animals were administered with gliclazide 50 mg/kg and act as a reference drug group. The remaining groups of the diabetic animals were administered with the newly synthesized dihydropyrimidine compounds in a single dose of 50 mg/kg orally using the oral gavage, daily for 7 days continuously. The blood glucose level was measured before and 72 hrs after nicotinamide-STZ injection, for confirmation of hyperglycemia and type 2 diabetes development. Results: Blood glucose levels were significantly (p<0.05) reduced after treatment with these derivatives. The mean percentage reduction for gliclazide was 50%, while that of synthesized compounds were approximately 36%. Conclusion: Our result suggests that the synthesized new DEEM derivative containing alkoxy group on the phenyl ring shows a significant lowering of glucose level compared to other derivatives.
Keywords: anti-Diabetic; blood glucose levels; dihydropyrimidine; hypoglycemic activity; Streptozotocin; type 2 diabetes mellitus

Crystal structure of a 1:1 co-crystal of the anti-cancer drug gefitinib with azelaic acid - George, Christy P.; Sangtani, Ekta; Gonnade, Rajesh G. (Acta Crystallographica Section E: Crystallographic Communications, 2020)
In the title co-crystal, C22H24ClFN4O3·C9H16O4, gefitinib (GTB; systematic name: quinazolin-4-amine) co-crystallizes with azelaic acid (AA; systematic name: nona-nedioic acid). The co-crystal has the monoclinic P21/n centrosymmetric space group, containing one mol-ecule each of GTB and AA in the asymmetric unit. A structure overlay of the GTB mol-ecule in the co-crystal with that of its most stable polymorph revealed a significant difference in the conformation of the morpholine moiety. The significant deviation in the conformation of one of the acidic groups of azelaic acid from its usual linear chain structure could be due to the encapsulation of one acidic group in the pocket formed between the two pincers of GTB namely, the morpholine and phenyl moieties. Both GTB and AA mol-ecules form N-H⋯O, O-H⋯N, C-H⋯O hydrogen bonds with C-H⋯F close contacts along with off-stacked aromatic π-π inter-actions between the GTB mol-ecules.

Tale of biphenyl and terphenyl substituents for structurally diverse ketiminato magnesium, calcium and germanium complexes - Kumar, Rohit; Yadav, Sandeep; Gour, Kritika; Sangtani, Ekta; Ranjan Dash, Soumya; Raja, Abhishekram; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemistry-An Asian Journal, 2020)
In this paper, we have used two N,O-ketiminato ligands (L1 and L2) with biphenyl and terphenyl substituent on the nitrogen atom. Deprotonation of L1 with KN(SiMe3)(2) and subsequent reaction with MgI2 led to a homoleptic dinuclear magnesium complex (1) with a Mg2O2 four-membered ring. Deprotonation with nBuLi and subsequent reaction with MgI2 afforded a unusual dinuclear magnesium complex (2) with a Mg2O2 ring. Extension of the ligand for calcium resulted in a trinuclear calcium complex (3) with six four-membered Ca2O2 rings. We could not isolate any chelating complex when L2 was used as a ligand, and only oxygen bound magnesium (4) and calcium (5) adducts were isolated. DFT studies were performed to understand this dissimilar behavior. More diverse results were obtained when lithiated L1 and L2 were treated with germanium dichloride. We were able to stabilize a monomeric germylene monochloride (7) with L1. However, with L2, an unusual ligand scrambling, and a C-C coupling take place, leading to the formation of a secondary carbocation with GeCl3- as a counter-anion (8). Besides, a germanium dichloride adduct (9) bound to the oxygen center of the ligand was obtained as the minor product.
Keywords: calcium; Germylene; ligand; Magnesium; X-ray Structure

Chemistry, anti-diabetic activity and structural analysis of substituted dihydropyrimidine analogues - Bairagi, Keshab M.; Younis, Nancy Safwat; Emeka, Promise Madu; Venugopala, Katharigatta N.; Alwassil, I, Osama; Khalil, Hany Ezzat; Sangtani, Ekta; Gonnade, Rajesh G.; Mohanlall, Viresh; Nayak, Susanta K. (Journal of Molecular Structure, 2021)
In an effort to identify an anti-diabetic agent, a series of methyl/ethyl 4-(hydroxyphenyl)-6-methyl-2-oxo/thioxo-1,2,3,4 tetrahydropyrimidine-5-carboxylate analogues (4a-h) have been synthesized, purified, and characterized by using Fourier-Transform Infrared Spectroscopy (FT-IR) and NMR (H-1 and C-13). The synthesized compounds were screened for anti-hyperglycemic activity using Streptozotocin (STZ) induced diabetic rat model. The anti-hyperglycemic activity of dihydropyrimidine (DHPM) compound is mainly analyzed with the variation of substituents present on the phenyl ring and urea/thiourea group on pharmacophoric features. Further, the crystal structure and supramolecular characteristics of two compounds 4c and 4f were analyzed through a single-crystal X-ray method and the Hirshfeld Surface Analysis, which shows hydrogen bonding through N-H center dot center dot center dot O and N-H center dot center dot center dot S interactions with the formation of ring motif in the crystal structure. It is interesting to note that among the title compounds, the 4a, 4e, 4f, and 4g significantly displayed a better hypoglycemic effect in vivo rat model study. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Dihydropyrimidine (DHPM); Hypoglycemia; Streptozotocin (STZ); Type-2 diabetes mellitus (T2DM)